Housing Affordability Woes and The State Of Developed Underdevelopment In Penang Island - Khoo, Khoo Suet Leng; Malek, Nor Malina; Mat Yasin, Suziana (Universiti Utara Malaysia, 2017)
Housing affordability is a critical issue in Malaysia.This issue is doubly challenging in states like Penang where its topographical make-up is divided into a mainland and an island. The dwindling stock of land in Penang Island has inevitably pushed up house prices.To compound this problem, a combination of policy and socio-economic changes has collectively hiked up the cost of buying a house on the island.This has hindered equal opportunities towards home ownership.Based on a development perspective, this paper attempts to contextualize current housing woes in Penang Island.This paper argues that Penang Island’s physical urban environment has ‘developed’ in terms of aesthetic values and appreciated in monetary terms but actual development in terms of a person’s ‘capability to function’ and enjoy a better quality of life is not progressing in tandem.A critical state of developed underdevelopment is currently unfolding on the island in terms of housing affordability.The recommendations of this paper will contribute towards shaping pragmatic housing policies.